PHENOMENON OF ‘FOREIGN AID AND ASSISTANCE’ IN THEORETICAL DISCOURSE: OLD AND NEW APPROACHES - Ezoza Akhmedova (Modern American Journals, 2025)
This paper provides a comprehensive examination of the evolution of foreign aid and assistance within international relations theory, tracing its development from early informal, religious, and philanthropic efforts to modern, institutionalized, and state-led mechanisms. The author critically reviews major theoretical frameworks-including realist, liberal, modernization, dependency, neoliberal institutionalist, postcolonial, and sustainable development approaches-highlighting their perspectives on the motivations, effectiveness, and consequences of aid. The discussion is enriched with empirical data, case studies, and references to key scholars such as Morgenthau, Keynes, Nye, Sen, and Sachs. The thesis also addresses contemporary trends such as the increasing complexity of the global aid architecture, the role of the International Development Association (IDA), and the emergence of non-Western donors. Special attention is given to interdisciplinary approaches in evaluating aid, including comparative, conflict, strategic, environmental, and non-Western studies. The work concludes by advocating for recipient-centered, sustainable, and inclusive models of aid in a multipolar world.
Keywords: Foreign aid, international assistance, theoretical frameworks, realism, liberalism, modernization theory, dependency theory, neoliberal institutionalism, postcolonial theory, sustainable development, International Development Association (IDA), aid effectiveness, comparative studies, conflict studies, strategic studies, environmental aid, non-Western donors, global development, recipient-centered models.